Wise Using Social Media in The Perspective of The Quran and Hadith - Muhammad Raihan Yazid; Muhammad Rafli Firdaus; Fuad Hilmi (UIN Sunan Gunung Djati Bandung, 2023)
In the current era of informatics (new media) development, many immoral acts in communication are a challenge as well as a threat to the harmony of social and state life in the unitary state of the Republic of Indonesia. As emphasized by M. Zia Al-Ayyubi, there are several types of negative content on social media that attack certain groups and individuals, such as: statements with provocative values, fraud, hate speech, SARA issues, religion and class (SARA). This article examines the ethics of Islamic communication in the perspective of the Koran, the urgency of Islamic communication ethics on social media in maintaining the integrity of the Unitary State of the Republic of Indonesia. In this study a qualitative approach was used using the Al Quran textbook/library research method, where verses related to communication ethics were collected, after which the authors analyzed and drew conclusions as a solution to good Islamic communication ethics given in the Al Quran. The results of this study indicate that the Qur'an provides guidelines for communication ethics, namely 1) communication must be based on truth and patience, 2) filter information when receiving (Tabayyun), 3) avoid reproaching each other differences, Communicating with good manners and language, and indirectly with good values.